Deaf Children's Moral Behavior, Moral Reasoning and Emotion Attribution. (31st January 2019) - Hao, Jian; Wu, Chunsha
Abstract: The present study examined deaf children's moral development with experimental tasks. Experiment 1 investigated lying and sharing behavior in 37 six- to 11-year-old deaf children, 39 age-matched hearing children and 33 twelve- to 16-year-old deaf adolescents who were matched with the hearing children on vocabulary ability. The results showed that the deaf children did not lie more but shared less than the hearing children. The deaf adolescents' sharing behavior was similar to the hearing children. Experiment 2 further investigated moral reasoning and emotion attribution among 20 deaf children and 30 age-matched hearing children. The results showed that the deaf children did not lag behind the hearing children in moral reasoning but did so with regard to attributing emotions to themselves in moral contexts. Therefore, the present study indicates that moral cognition might be sufficient for deaf children to avoid rule-breaking behavior but insufficient for them to show prosocial behavior.